2008
DOI: 10.1039/b801226a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative humidity and CO(g) on the O3-initiated oxidation reaction of Hg0(g): kinetic & product studies

Abstract: Ozone is assumed to be the predominant tropospheric oxidant of gaseous elemental mercury (Hg0(g)), defining mercury global atmospheric lifetime. In this study we have examined the effects of two atmospherically relevant polar compounds, H2O(g) and CO(g), on the absolute rate coefficient of the O3-initiated oxidation of Hg0(g), at 296 +/- 2 K using gas chromatography coupled to mass spectrometry (GC-MS). In CO-added experiments, we observed a significant increase in the reaction rate that could be explained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…Despite the potential significant role of heterogeneous Hg reactions on atmospheric Hg chemistry and model simulations [37,92], scare data is available on mercury reactions and equilibrium processes on atmospheric surfaces such as aerosols [48]. A systematic understanding of the surface chemistry of Hg is extremely difficult [48,93] due to the varying concentration, size distribution and composition of aerosols at different locations, times and meteorological conditions [94,95].…”
Section: Heterogeneous Redox Reactions Of Hgmentioning
confidence: 99%
“…Despite the potential significant role of heterogeneous Hg reactions on atmospheric Hg chemistry and model simulations [37,92], scare data is available on mercury reactions and equilibrium processes on atmospheric surfaces such as aerosols [48]. A systematic understanding of the surface chemistry of Hg is extremely difficult [48,93] due to the varying concentration, size distribution and composition of aerosols at different locations, times and meteorological conditions [94,95].…”
Section: Heterogeneous Redox Reactions Of Hgmentioning
confidence: 99%
“…It has been postulated that intermediate products like HgO 3 could lead to the formation of stable (HgO) n oligomers or HgO (s) via decomposition to OHgOO (g) (Subir et al, 2011), but these must be stabilized through heterogeneous reactions on atmospheric aerosols (Calvert and Lindberg, 2005), and the associated mechanism is unlikely to be significant in the atmosphere (Hynes et al, 2009). A gas-phase reaction has been reported in chamber studies (Hall, 1995;Pal and Ariya, 2004;Sumner et al, 2005;Snider et al, 2008;Rutter et al, 2012), but this is likely to have been influenced by the walls of the chamber (as seen in Pal and and presence of secondary organic aerosols (in Rutter et al, 2012). j Atmospheric concentrations of I and IO (Dix et al, 2013;Prados-Roman et al, 2015;Volkamer et al, 2015) are too low for these reactions to be significant.…”
Section: Chemical Mechanismmentioning
confidence: 99%
“…Our calculated rate constants in wet reaction with two and one water molecule are 4.76 × 10 -20 and 1.11 × 10 -25 cm 3 molec -1 s -1 , respectively, that are comparable with the experimental vales. Experimental values predict that rate constant increases with relative humidity [12][13] Fig. 6, it can be seen that the rate constant k increases rapidly with the number of water molecule in reaction.…”
Section: Calculation Of Rate Constantsmentioning
confidence: 92%
“…The effect of water molecules on gas phase reaction has not been extensively studied. Ariya 12 and Snider 13 found that the rate constant varied between 3 × 10 -19 and 30 × 10 -19 cm 3 molelules -1 s -1 as the relative humidity was varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation